Cholecystokinin metabolism in normal man and patients with duodenal ulcer. - Ramus, N. I. (Royal College of Surgeons of England, 1982)
Using two cholecystokinin (CCK) radioimmunoassays CCK has been shown to be heterogeneous (CCK-33 and CCK-8) after both exogenous infusion and endogenous release. CCK-39 (CCK variant) was not separated after endogenous CCK stimulation but was identified after the exogenous infusion of 16% pure CCK. The disappearance half-time of 16% pure CCK has been shown to be 2.4 min and one major organ of catabolism identified--the kidney. Degradation of CCK by whole blood occurred after standing for 2 h, but if separation was carried out immediately serum could be left for 6 h before any further degradation took place. Serum appeared to retain its CCK activity more reliably than plasma. Abnormalities in CCK release in duodenal ulcer disease, which are further altered by highly selective vagotomy (HSV), have been demonstrated. Pancreatic exocrine function was not significantly altered by HSV. CCK release and disappearance are more rapid in patients with duodenal ulceration. This observation may be aetiologically important since unopposed postprandial hypergastrinaemia in the absence of effective inhibition by CCK might lead to increased gastric acid production.